ПСИХОЛОГІЧНІ АСПЕКТИ ПРОФЕСІЙНОЇ ПІДГОТОВКИ ВЧИТЕЛЯ ПОЧАТКОВИХ КЛАСІВ (Педагогіка вищої та середньої школи, 2001)
Professional training of a primary school teacher is considered to he many-sided. This article touches upon psychological aspects of this problem. Analyzing the main conditions for development of a teacher as a professional the authors stresses on the following: personal orientation on a concrete pupil, psychological competence and self-management of a primary class teacher.